The treatment of segmental tibial fractures: does patient preference differ from surgeon choice?. Issue 10 (October 2017) - Little, Z.; Smith, T.O.; McMahon, S.E.; Cooper, C.; Trompeter, A.; Pearse, M.; Britten, S.; Rogers, B.; Sharma, H.; Narayan, B.; Costa, M.; Beard, D.J.; et al.
Abstract: Introduction: Segmental tibial fractures are complex injuries with a prolonged recovery time. Current definitive treatment options include intramedullary fixation or a circular external fixator. However, there is uncertainty as to which surgical option is preferable and there are no sufficiently rigorous multi-centre trials that have answered this question. The objective of this study was to determine whether patient and surgeon opinion was permissive for a randomised controlled trial (RCT) comparing intramedullary nailing to the application of a circular external fixator. Materials and methods: A convenience questionnaire survey of attending surgeons was conducted during the United Kingdom's Orthopaedic Trauma Society annual meeting 2017 to determine the treatment modalities used for a segmental tibial fracture (n = 63). Patient opinion was obtained from clinical patients who had been treated for a segmental tibial fracture as part of a patient and public involvement focus group with questions covering the domains of surgical preference, treatment expectations, outcome, the consent process and follow-up regime (n = 5). Results: Based on the surgeon survey, 39% routinely use circular frame fixation following segmental tibial fracture compared to 61% who use nail fixation. Nail fixation was reported as the treatment of choice for a closed injury in a healthy patient in 81% of surgeons, and by 86% for a patient with a closed fracture who was obese. Twenty-one percent reported that they would use a nail for an open segmental tibia fracture in diabetics who smoked, whilst 57% would opt for a nail for a closed injury with compartment syndrome, and only 27% would use a nail for an open segmental injury in a young fit sports person. The patient and public preference exercise identified that sleep, early functional outcomes and psychosocial measures of outcomes are important. Conclusion: We concluded that a RCT comparing definitive fixation with an intramedullary nail and a circular external fixator is justified as there remains uncertainty on the optimal surgical management for segmental tibial fractures. Furthermore, psychosocial factors and early post-operative outcomes should be reported as core outcome measures as part of such a trial.